Investigating the Association between Blood Transfusion and Hepatitis C infection During Pregnancy - Aasma Naz, Yasmeen Rasheed Bhutto, Kiran Memon, Amanullah Bhutto, Rukhsana Saboor, Durgha Devi, Aamir Ramzan, Kiran Aamir, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Aim was determine the association between blood transfusion and hepatitis C infection during pregnancy. Study Design: Descriptive study Place and Duration: Peoples University of Medical and Health Sciences Nawabshah. Feb 2021-Jan 2022 Methods: Total 171 pregnant women of age 18-40 years were presented in this study. The patient's age, parity, and other risk factors such as previous operations, vaginal births, and transfusions were recorded, and a thorough physical examination was conducted. Anti HCV positivity on Immunochromatography Test (ICT) was confirmed by Elisa in patients undergoing normal prenatal evaluation. The data collection process followed a carefully crafted proforma. To examine the information, we used SPSS 22.0. Results: Among 171 patients, 82 (47.95%) females had age 18-25 years, 57 (33.3%) patients had age 26-35 years and 32 (18.7%) females had age 36-40 years. 75 (43.6%) cases had BMI >25kg/m2. 49 (28.7%) cases were primigravida and rest 120 (71.3%) cases were multi-gravida. We found 15 (8.8%) cases of HCV positive. Among 15 cases, 8 cases had history of blood transfusion, 3 had history of surgery, 2 cases because of injections and 2 cases had jaundice. Among 15 positive cases, majority of the cases had age 26-35 years. Conclusion: We found in this that blood transfusion is a significantly risk factor for HCV among pregnant females. There is need to educated pregnant females at institution to avoid its prevalence during pregnancy. Keywords: Pregnant Females, Blood transfusion, HCV, Parity